2009
DOI: 10.1097/pgp.0b013e3181895539
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Neuroendocrine Expression in Undifferentiated Carcinoma of the Endometrium

Abstract: Carcinomas with neuroendocrine (NE) differentiation have been associated with poor outcome in different organs. The purpose of this study was to evaluate the presence and significance of NE expression in a series of 46 undifferentiated endometrial carcinomas diagnosed between 1988 and 2005. NE expression was studied by immunohistochemistry including synaptophysin, chromogranin, and/or CD56. The patients' age ranged from 30 to 84 years (mean 55). Staging information was available for 45 cases and according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…UCs can show focal neuroendocrine features and staining with neuroendocrine-related markers without any impact on clinical outcome. 17 In our study, 3 of 10 cases showed focal (less than 10%) synaptophysin and/or chromogranin staining. We would classify a tumor that shows strong and diffuse staining for neuroendocrine markers as a neuroendocrine carcinoma rather than UC.…”
Section: Discussionmentioning
confidence: 94%
“…UCs can show focal neuroendocrine features and staining with neuroendocrine-related markers without any impact on clinical outcome. 17 In our study, 3 of 10 cases showed focal (less than 10%) synaptophysin and/or chromogranin staining. We would classify a tumor that shows strong and diffuse staining for neuroendocrine markers as a neuroendocrine carcinoma rather than UC.…”
Section: Discussionmentioning
confidence: 94%
“…The latter tumor has been characterized relatively recently as a clinically aggressive and histologically distinctive entity typically comprising relatively monomorphous medium to large cells that are arranged in sheets without evidence of gland formation [2]. Additional histologic features that may be focally present in some cases include marked nuclear pleomorphism, spindle cells, abrupt keratinization, myxoid stroma, prominent tumor-infiltrating lymphocytes (TILs), and rhabdoid cells [3][4][5][6]. A variable proportion of UEC are associated with a low-grade (grade 1 or 2) endometrioid carcinoma, and these cases have been classified as dedifferentiated or combined carcinomas [5,7].…”
Section: Introductionmentioning
confidence: 98%
“…However, neuroendocrine carcinoma displays characteristic chromatin pattern and typically shows positivity for chromogranin, synaptophysin, NSE, and/or CD 56 in > 10% of the cells. 42 In addition, keratin expression tends to be more prominent than in undifferentiated carcinoma. Serous carcinoma.…”
Section: S35mentioning
confidence: 99%
“…Chromogranin and/or synaptophysin can be focally positive (≤10% of cells) but this finding does not warrant designation as a neuroendocrine carcinoma. 42 ER/PR expression is usually low or absent. Up to 80% of the tumors are PAX-8 negative.…”
Section: S35mentioning
confidence: 99%